2017
DOI: 10.1007/s40685-016-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replenishment and backroom on retail shelf-space planning

Abstract: Shelf-space optimization models support retailers in making optimal shelf-space decisions. They determine the number of facings for each item included in an assortment. One common characteristic of these models is that they do not account for in-store replenishment processes. However, the two areas of shelf-space planning and in-store replenishment are strongly interrelated. Keeping more shelf stock of an item increases the demand for it due to higher visibility, permits decreased replenishment frequencies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Hübner, 2011;Irion et al, 2012), some assume a deterministic demand (e.g. Yücel et al, 2009;Hübner and Schaal, 2017), some consider limited shelf space (e.g. Kök et al, 2015), different costs and margin components and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hübner, 2011;Irion et al, 2012), some assume a deterministic demand (e.g. Yücel et al, 2009;Hübner and Schaal, 2017), some consider limited shelf space (e.g. Kök et al, 2015), different costs and margin components and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Their approach provides only near-optimal solutions for the shelf-assignment problem with a predefined assortment. Hübner and Schaal (2017) integrate assortment planning into shelf-space and replenishment planning. They develop an iterative solution approach.…”
Section: Retail Assortment Planningmentioning
confidence: 99%
“…Products shipped already priced in cage pallets and ready for display would need to be placed near the entrances so that they can be wheeled in with minimal disturbance (Buttle, 1984). Moreover, a pallet shelf is a very convenient solution as they are reusable and can be moved to other locations for better accessibility in the store (Hübner and Schaal, 2017).…”
Section: Palletmentioning
confidence: 99%
“…Also studies on "Warehouse Operator Selection" (Korpela, Lehmusvaara, & Nisonen, 2007), "Equipment Selection" (Dağdeviren, 2008) and "Packaging Selection" (Tümenbatur, 2016) are found. When the studies on "Storage Rack Systems" are investigated, most of the studies found are related to inventory optimization as listed in Table 1 like "Order Picking" (Hwang & Cho, 2006), (Tunç, Kutlu, Zincidi, & Atmaca, 2008), (Ofluoğlu & Baki, 2016) and "Shelf-Space Allocation" (Özcan, 2010), (Geismar, Dawande, Murthi, & Sriskandarajah, 2015), (Tsaia & Huang, 2015), (Hübner & Schaal, 2017) . Matson & White (1981) focused on optimization procedures for the design and selection of storage system alternatives, including block stacking, single-deep and double-deep pallet rack, and deep lane storage.…”
Section: Literature Reviewmentioning
confidence: 99%